Corrections to the classification of the Neotropical ant-like stone beetles misplaced in Euconnus Thomson (Coleoptera, Staphylinidae, Scydmaeninae). Part 1. - Jałoszyński, Paweł (Zootaxa, 2020)
Taxonomic placement of five Neotropical species of Glandulariini, previously misplaced in Euconnus, is corrected based on examination of type specimens. Euconnus brunneus Franz is placed in Tridensius gen. n.; Euconnus sibyllensis Franz in Sibylloconnus gen. n.; Euconnus fimbriatulus Reitter in Protandroconnus Franz; Euconnus johnsoni Franz in Amimoscydmus Jałoszyński; and Scydmaenus asserculatus L.W. Schaufuss (placed in Euconnus by Csiki and Franz) in Venezolanoconnus Franz. Each species is redescribed: Tridensius brunneus (Franz) comb. n., Sibylloconnus sibyllensis (Franz) comb. n., Protandroconnus fimbriatulus (Reitter) comb. n., Amimoscydmus johnsoni (Franz) comb. n., and Venezolanoconnus asserculatus (L.W. Schaufuss) comb. n. A key to identification of the new Neotropical genera is given.